Educational Management Based on Local Wisdom (Descriptive Analytical Studies of Culture of Local Wisdom in West Kalimantan) - Hamid Darmadi (STKIP Singkawang, 2018)
Education is a deliberate and planned deliberate effort to foster the development and potential of individual self-learners